2020
DOI: 10.1101/2020.04.21.052951
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nicotinamide promotes differentiation of pancreatic endocrine progenitors from human pluripotent stem cells through poly (ADP-ribose) polymerase inhibition

Abstract: The generation of pancreatic endocrine progenitor cells is an important step in the differentiation of beta cells from human pluripotent stem cells (hPSC). This stage is marked by the expression of Nkx6.1, a transcription factor with well understood downstream targets but with unclear upstream regulators. In hPSC differentiation, Nkx6.1 is strongly induced by nicotinamide, a derivative of vitamin B3, which has three known functions within a cell. Nicotinamide inhibits two classes of enzymes known as poly-ADP-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…Nicotinamide has historically been used to augment pancreatic β-cell differentiation and to protect islet cells from toxic insults, due to its antioxidant properties. Studies showed that cells exposure to nicotinamide is essential for robust nkx6.1 expression in hiPSC differentiation to pancreatic endocrine progenitors, acting predominantly through PARP (poly-ADPribose polymerases) inhibition [167,168]. Thowfeequ et al [169] showed that the addition of betacellulin and nicotinamide to the modified differentiation protocol sustained PDX1 expression and induced pancreatic β-cell differentiation in human ES cell line.…”
Section: Mature β-Cellsmentioning
confidence: 99%
“…Nicotinamide has historically been used to augment pancreatic β-cell differentiation and to protect islet cells from toxic insults, due to its antioxidant properties. Studies showed that cells exposure to nicotinamide is essential for robust nkx6.1 expression in hiPSC differentiation to pancreatic endocrine progenitors, acting predominantly through PARP (poly-ADPribose polymerases) inhibition [167,168]. Thowfeequ et al [169] showed that the addition of betacellulin and nicotinamide to the modified differentiation protocol sustained PDX1 expression and induced pancreatic β-cell differentiation in human ES cell line.…”
Section: Mature β-Cellsmentioning
confidence: 99%
“…Likewise, it has been reported that taurine, an essential amino acid, affects the pancreas development, enhances and maintains the endocrine function, and increases the size and number of the islets (El Idrissi et al, 2009). Also, NIC, a form of vitamin B, acts as a poly (ADP-ribose) polymerase inhibitor that is used to promote MSCs homing functional PE/IPCs and preserve the islet viability and function by protection of NAD + /NADH ratio (Yang et al, 2015;Woodford et al, 2020). Thus, both taurine and NIC are used during differentiation into PE/IPCs and in vitro preservation.…”
Section: Chapter V Discussionmentioning
confidence: 99%